(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
Interview carried out by the editors of the Revista de Ensino em Artes, Moda e Design to GT Consumo de Moda. Interview granted on February 4, 2023, at Maringá – Olga Maria Coutinho Pepece. Interview granted on March 30, 2023, in Rio de Janeiro – Ana Paula Celso de Miranda.